KEPERCAYAAN KONSUMEN TERHADAP NIAT BELI PRODUK FASHION YANG DIPASARKAN MELALUI MEDIA SOSIAL FACEBOOK ( STUDI PADA MAHASISWA S1 FISIP UNDIP SEMARANG ) - Sari Listyorini (JURNAL ILMU SOSIAL, 2015)
Businesses increasingly globalized trade with the technology in the application of product marketing . By using the internet, consumers are able to purchase goods or products freely without attachment time. The form of marketing on the Internet is known as e - commerce or electronic commerce. E commerce or electronic commerce is spread, purchasing, sales, marketing goods and services over electronic systems such as the Internet or television, www, or other computer networks such as the social media one. The more rapid development of e-commerce today is strongly influenced by the people's confidence in e –commerce.This study aims to determine consumer confidence ( ablity ,benevolence and integrity) of the purchase intention fashion products on the Facebook social media on student S1 FISIP Undip Semarang .Based on a simple regression analysis showed that the ability ( ability ) sellers a significant effect on consumer purchasing intention of fashion products , benevolence ( kindness ) shop online seller does not significantly influence consumers' purchasing intention of fashion products , integrity ( integrity ) shop online sellers a significant effect on purchase intentions consumer fashion products . The results of multiple regression showed that ablity , benevolence and integrity towards purchase intention poduk fashion on the Facebook social media simultaneously significant effect .Advice can be delivered in this study is an online shop needs to use some social media other than Facebook, need to pay attention to product quality, conformance with product photos, and timeliness need to be considered in serving the wishes of potential customers, need to improve in terms of honesty transaction.